(untitled) (Religious dialogue and cooperation, 2025)
Estonia has been repeatedly called the least religious country in Europe or even the whole world. The Estonian mainstream media and politics mainly resonate with the identification of Estonians as a rational high-tech and science-oriented nation. Although the number of people who believe in biblical God and/or feel affiliated to any canonical religion is indeed low according to representative polls, there are numerous other forms for communicating with the numinous (e.g., in the form of protective angels, spirit animals, nature spirits, spirits of dead relatives, or pets who give spiritual guidance) observable in the Estonian society. Based on personal experience narratives from the recent decade, this article will give an overview of supernatural helpers and protectors with whom people in Estonia communicate. Answers will be sought to the following questions: Who are these beings? From which traditions do they stem? Which ways of communicating with them are practiced? What are the differences compared to older layers of religion? This paper will demonstrate a recent heterogenous pluralism, presented in the co-existence and fluctuation of – partly situational – beliefs in various supernatural figures, and try to locate these findings in the current (post)secularization debates. The author concludes that such contemporary models of religious beliefs and practices are not necessarily replacing the traditional ones but rather recycle already existing religious ideas in somewhat modified configurations that are adjusted to the contemporary needs. Despite the rather polarized view of religion and science in the mainstream media and political discourse, the empirical material shows that such vernacular beliefs and practices may build symbioses with scientific conceptions of the world.